Conserved core microbiota in managed and free-ranging Loxodonta africana elephants - Thorel, Milan; Obregon, Dasiel; Mulot, Baptiste; Maitre, Apolline; Mateos-Hernandez, Lourdes; Moalic, Pierre-Yves; Wu-Chuang, Alejandra; Cabezas-Cruz, Alejandro; Leclerc, Antoine (Frontiers in Microbiology, 2023)
The gut microbiota plays a crucial role in animal health and homeostasis, particularly in endangered species conservation. This study investigated the fecal microbiota composition of European captive-bred African savanna elephants (Loxodonta africana) housed in French zoos, and compared it with wild African savanna elephants (Budd et al., 2020). Fecal samples were collected and processed for DNA extraction and amplicon sequencing of the 16S rRNA gene.The analysis of a and b diversity revealed significant effects of factors such as diet, daily activity, and institution on microbiota composition. Specifically, provision of branches as part of the diet positively impacted microbiota diversity. Comparative analyses demonstrated distinct differences between captive and wild elephant microbiomes, characterized by lower bacterial diversity and altered co-occurrence patterns in the captive population. Notably, specific taxa were differentially abundant in captive and wild elephants, suggesting the influence of the environment on microbiota composition. Furthermore, the study identified a core association network shared by both captive and wild elephants, emphasizing the importance of certain taxa in maintaining microbial interactions. These findings underscore the impact of environment and husbandry factors on elephant gut microbiota, highlighting the benefits of dietary enrichment strategies in zoos to promote microbiome diversity and health.The study contributes to the broader understanding of host-microbiota interactions and provides insights applicable to conservation medicine and captive animal management.